School and Language Policy - K C, Laxman (Mangal Research Journal, 2020)
This paper attempts to explore how and why language policies are made at schools. Language in education is the everlasting burning issue in this world of globalization era. There are several agencies to make, practice and influence language policy in education and other dimensions of the society. For educational dimension, school is an important agency to make and practice language policy. In the context of Nepal, nowadays schools are formulating their own language policies independently and abiding proximal agencies. This paper attempts to explore the lived experiences of the school teachers as administrators and teachers. Two secondary school head teachers, one from community school and another from institutional school were interviewed and had the informal communication as well. Two other teachers were also interviewed, observed and interacted. Schools were found to make language policy considering three aspects: institutional promotion, parents' interest, and contemporary living world's English language ideology. As they reported, students are not so important agency to contribute school language policy making process but parents and their interests are highly prioritized. They were reported that they did not consider national language policy, multilingual reality, diversity, language identity and cognitive investment of the learners. Teachers were educated in monolingual education, so they preferred monolingual language policy.